The Robust Detection and Spatial Distribution of Acetaldehyde in Orion KL: Atacama Large Millimeter/submillimeter Array Observations and Chemical Modeling - Miwha Jin; Anthony J. Remijan; Robin T. Garrod; Giseon Baek; Martin Cordiner; Steven Charnley; Eric Herbst; Jeong-Eun Lee (The Astrophysical Journal, 2025)
Despite the organic molecule inventory detected in the Orion Kleinmann–Low Nebula (Orion KL), acetaldehyde (CH _3 CHO)—one of the most ubiquitous interstellar aldehydes—has not been firmly identified with millimeter-wave interferometry. We analyze extensive Atacama Large Millimeter/submillimeter Array archival data sets (142–355 GHz) to search for acetaldehyde, revealing two distinct acetaldehyde emission peaks and one component with more complex kinematic structures. One peak aligns with MF10/IRc2, where emissions of other O-bearing complex organic molecules are rarely reported, while the other is coincident with the ethanol peak in the southwest region of the hot core. The MF10/IRc2 detection suggests unique chemistry, possibly influenced by repeated heating events. In contrast, codetection with ethanol indicates an ice origin and suggests a potential chemical relationship between the two species. We determine acetaldehyde column densities and kinetic temperatures toward these two peaks under local thermodynamic equilibrium assumptions and compare its distribution with ethanol and other molecules that have an aldehyde (HCO) group, such as methyl formate, glycolaldehyde, and formic acid. Toward the ethanol peak, the observed abundance ratios between HCO-containing species are analyzed using a chemical model. The model suggests two key points: (1) the destruction of ethanol to form acetaldehyde in the ice may contribute to the observed correlation between the two species; and (2) a long cold-collapse timescale and a methyl formate binding energy similar to or lower than water are needed to explain the observations. The relative abundance ratios obtained from the model are highly sensitive to the assumed kinetic temperature, which accounts for the high spatial variability of the aldehyde ratios observed toward Orion KL.